2018
DOI: 10.1016/j.jhealeco.2018.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Shale gas development and infant health: Evidence from Pennsylvania

Abstract: This research exploits the introduction of shale gas wells in Pennsylvania in response to growing controversy around the drilling method of hydraulic fracturing. Using detailed location data on maternal addresses and GIS coordinates of gas wells, this study examines singleton births to mothers residing close to a shale gas well from 2003 to 2010 in Pennsylvania. The introduction of drilling increased low birth weight and decreased term birth weight on average among mothers living within 2.5 km of a well compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
103
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 125 publications
(111 citation statements)
references
References 107 publications
(179 reference statements)
8
103
0
Order By: Relevance
“…It was noted that the design "relies heavily on the assumption that the characteristics of mothers who live close to a permitted well are similar to those who live close to an actual existing well" (Hill, 2012, p. 4). While the results suggested UNGD exposure increases low birth weight and small for gestational age prevalence by 25% and 17%, respectively, and the author stated that this study provides evidence that UNGD detrimentally affects foetal development (Hill, 2012), numerous explanations (e.g., other changes in the area, including in/out migration) could be attributed to this rather than the explanation of pollution associated with UNGD. This study presents significant methodological limitations compared to the previous birth outcome study that was discussed.…”
mentioning
confidence: 69%
See 4 more Smart Citations
“…It was noted that the design "relies heavily on the assumption that the characteristics of mothers who live close to a permitted well are similar to those who live close to an actual existing well" (Hill, 2012, p. 4). While the results suggested UNGD exposure increases low birth weight and small for gestational age prevalence by 25% and 17%, respectively, and the author stated that this study provides evidence that UNGD detrimentally affects foetal development (Hill, 2012), numerous explanations (e.g., other changes in the area, including in/out migration) could be attributed to this rather than the explanation of pollution associated with UNGD. This study presents significant methodological limitations compared to the previous birth outcome study that was discussed.…”
mentioning
confidence: 69%
“…Some have concluded that there is a relationship between congenital heart defects and the density of, as well as proximity to, UNGD , and that UNGD exposure increases prevalence of certain birth outcomes (Hill, 2012). Conversely, Fryzek et al's (2013) study about childhood cancer in relation to hydraulic fracturing found that the number of cancer cases was no higher than that which could generally be expected in the study area.…”
Section: Ungd and Human Healthmentioning
confidence: 89%
See 3 more Smart Citations